Indonesian Language Learning Strategies for Students Speaking Mandarin in the VUCA Era - Rahmawati, Ida Yeni; Suyitno, Imam; Andajani, Kusubakti (UM Purwokerto Press, 2024)
In this fast-paced era, there are many changes, uncertainties, challenges, and ambiguities in various aspects, especially in the process of learning Indonesian for foreign speakers of child age. Therefore, this study aims to describe the results of exploration related to Indonesian language learning strategies for Mandarin-speaking students in an era of volatility, uncertainty, complexity, and ambiguity. The research method used is descriptive qualitative. Primary data sources were obtained from Indonesian language teachers at the Jakarta Taipei School Cooperation Education Unit. Data collection was obtained through interviews, observations, and document analysis. The data analysis of this study used the Miles and Huberman model which consists of three stages including data reduction from data collection results, data presentation, and drawing conclusions and verification. The results of this study indicate that there are modifications to learning objectives, needs analysis, materials, methods, media, learning resources, and evaluation of learning that have been adjusted to the characteristics of students, in this case, Mandarin-speaking foreign students. Thus, it can be concluded that the Indonesian language learning strategy for Mandarin-speaking students in this era has undergone many changes, with the aim of being more adaptive, innovative, and responsive in accordance with the needs of the times.